Description of the male of Eucyphonia festiva (Hemiptera: Membracidae) and a reassessment of the distribution of the species - Forero, Dimitri; Rodríguez-Serrano, Juanita (Zootaxa, 2026)
The genus Eucyphonia Sakakibara, 1968 includes ten species distributed in South America. Besides external pronotal morphology, male genitalia is key to help delimit the species within the genus. Eucyphonia festiva Rodríguez-Serrano & Forero, 2019, a species described from the Orinoquia piedmont in Colombia, was known only from the female holotype. The discovery of additional specimens of E. festiva, including males, allows us to describe the male genitalia. In addition, we provide novel data on the distribution of this species documenting a wider occurrence on the Orinoquia foothills in Colombia, and newly record this species from an unknown locality in Brazil, probably corresponding to an area in the Amazon basin. Finally, plant associations are discussed based on label data from specimens, showing that several specimens from Colombia from separate collection events were found associated with unidentified species of Melastomataceae.